Sixth graders in Israel recount their experience of verbal abuse by teachers in the classroom. (January 2017) - Geiger, Brenda
Abstract: Aim: This study adopts a children's rights perspective stated in Articles 3, 12, 19, 28 of the Convention on the Rights of Children (1989) with the goal of listening to Israeli children articulate their experience of verbal abuse by teachers in 6th grade classrooms Methods: A purposeful sample of sixty students was individually interviewed and content analysis was performed following Strauss' (1987) constant comparative method. Results: Students reported teachers' yelling, name-calling and put-downs when failing to pay attention, complete their work, or obtain good grades. They condemned teachers as particularly hurtful and cruel for publically humiliating them in class. However, awareness of teachers' authority and fear of reprisal led to students' silence and reluctance to report the abuse to their parents or principal. Covert opposition was nevertheless exhibited as students engaged in a silent monologue telling teachers they had no right to mistreat them (females), silently cursing (males) and/or withdrawing participation (both genders). Repeated public humiliation and scapegoating resulted in the loss of interest in teacher's opinion and school and on rare occasions to the direct verbal confrontation or acting-out behaviour of the abused student. Conclusion: This study stresses the importance of gaining insight into the world of children by having them articulate their experience and denounce any form of abuse by teachers in the classroom. A child-safe school culture that listen to children's view and make them feel safe when reporting any form of abuse in the classroom are preconditions to serving children's best interests and wellbeing in schools.